2022
DOI: 10.3389/fpubh.2022.890960
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of the Moving to Emptiness Technique on Clients Who Need Help During the COVID-19 Pandemic: A Real-World Study

Abstract: With Western therapeutic techniques prevailing in Chinese therapies, some techniques that include Chinese traditional cultural features are required since some cultural factors are not considered in the Western method. Our study introduced a new technique, the moving to emptiness technique (MET), which combines Western structural progress and core factors of Chinese culture. Seventeen therapists treated 107 clients with the MET. Clients reported their target symptoms initially, and therapists helped them trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In this reactive chain, elderly adults' great concerns for the family can strengthen their nervousness about imminent issues. Besides medication treatment, mindfulness therapy (MT), acceptance and commitment therapy (ACT), moving to emptiness (MET) and cognitive-behavioral therapy (CBT) are effective in anxiety mitigation ( 48 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this reactive chain, elderly adults' great concerns for the family can strengthen their nervousness about imminent issues. Besides medication treatment, mindfulness therapy (MT), acceptance and commitment therapy (ACT), moving to emptiness (MET) and cognitive-behavioral therapy (CBT) are effective in anxiety mitigation ( 48 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that pharmacotherapy, behavior therapy, or simple expressive writing can effectively mitigate daily anxiety ( 56 , 58 ). Additionally, the “Moving to Emptiness Therapy Technique” based on Chinese culture has also shown excellent treatment effects for mental health problems ( 59 ). These methods should be considered in psychological intervention programs for high school students.…”
Section: Discussionmentioning
confidence: 99%
“…Another recently reported body-mind treatment is the Moving to Emptiness Technique, which draws from core elements of traditional Chinese practice combined with western structural process. This technique helps clients remove their symptoms by means of transferring their target symptoms into perceivable objects and move them into a psychological emptiness realm through a series of embodied operations (60,61). Comprehensive healing options can provide appropriate and personalized treatment that allow individuals to heal themselves and transform their suffering.…”
Section: Discussionmentioning
confidence: 99%